Spectacular science : a book of poems - Hopkins, Lee Bennett; Halstead, Virginia (Simon & Schuster Books for Young Readers, 1999)
A collection of poems about science by a variety of poets, including Carl Sandburg, Valerie Worth, and David McCord.